Nursing consultations and control of diabetes in general practice: a retrospective observational study - Murrells, Trevor (Br J Gen Pract, 2015)
BACKGROUND: Diabetes affects around 3.6 million people in the UK. Previous research found that general practices employing more nurses delivered better diabetes care, but did not include data on individual patient characteristics or consultations received. AIM: To examine whether the proportion of consultations with patients with diabetes provided by nurses in GP practices is associated with control of diabetes measured by levels of glycated haemoglobin (HbA1c). DESIGN AND SETTING: A retrospective observational study using consultation records from 319 649 patients with diabetes from 471 UK general practices from 2002 to 2011. METHOD: Hierarchical multilevel models to examine associations between proportion of consultations undertaken by nurses and attaining HbA1c targets over time, controlling for case-mix and practice level factors. RESULTS: The proportion of consultations with nurses has increased by 20% since 2002 but patients with diabetes made fewer consultations per year in 2011 compared with 2002 (11.6 versus 16.0). Glycaemic control has improved and was more uniformly achieved in 2011 than 2002. Practices in which nurses provide a higher proportion of consultations perform no differently to those where nurse input is lower (lowest versus highest nurse contact tertile odds ratio [OR] [confidence interval {95% CI}]: HbA1c ≤53 mmol/mol (7%) 2002, 1.04 [95% CI = 0.87 to 1.25] and 2011, 0.95 [95% CI = 0.87 to 1.03]; HbA1c ≤86 mmol/mol (10%) 2002, 0.97 [95% CI = 0.73 to 1.29] and 2011, 0.95 [95% CI = 0.86 to 1.04]). CONCLUSION: Practices that primarily use GPs to deliver diabetes care could release significant resources with no adverse effect by switching their services towards nurse-led care.